PERANAN KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DALAM MENCEGAH TERJADINYA PELANGGARAN PETUGAS PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KELAS II A WATAMPONE (PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM) - Sakka, Jihan Putri Ramadani; Fajar, Fajar; Fahri, Marjana (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2024)
This research aims to analyze the form of regulation and provision of ethical sanctions given to correctional officers who violate positive law and Islamic law and the role of the ministry of law and human rights in preventing violations by correctional officers at the Class II A Watampone Penitentiary. In the research, the author uses qualitative research, namely a type of research that qualitatively describes the object being discussed according to the reality that exists in society. The results of the research show that the role of the Ministry of Law and Human Rights is that the success of correctional officers in carrying out their duties of service, guidance and mentoring of correctional inmates, management of confiscated and confiscated objects as well as in daily life interactions, one of which is determined by moral integrity and exemplary attitudes and behavior of correctional employees. Keywords: Role, Ministry of Law and Human Rights, Correctional Institutions